Nonfamilial unilateral aplasia of the submandibular gland: A rare finding - Neeraj Kumar Dhiman; Ajit Kumar Vishwakarma; Vishal Verma; Shankar Singh (Wolters Kluwer Medknow Publications, 2018)
Congenital absence of the major salivary gland is a rare disorder, and the cause of absence has not been determined yet. In literature, disorder has been described to affect the submandibular and parotid gland along with multiple other facial developmental anomalies. Most commonly, congenital aplasia of submandibular gland is associated with compensatory hypertrophy of contralateral submandibular gland. Clinically, patients may be asymptomatic or may present with dryness of the mouth, difficulty in chewing and swallowing, and dental caries. We present a case of 34-year-old female with right submandibular gland aplasia associated with stone in the left submandibular duct causing proximal dilatation incidentally detected in the computed tomography.